Pengaruh Benefit dan Program terhadap Loyalitas IM3 @School di Komunitas Sekolah Jakarta Selatan - Rahadiyoso Arba Feria; Muchsin Saggaff Shihab (Program Studi Magister Manajemen FE Unsri, 2011)
This study aims to analyze the effect of benefits and program of IM3 @ school community on customers’ loyalty. This research is descriptive-quantitative in nature. Using convenience sampling technique, total sample of 200 respondents were obtained. Data were analyzed using statistical analysis. The result indicated that both the benefit and program of IM3@ school were found to have a direct influence on loyalty. The benefit was found to have a greater effect on loyalty. It is recommended that the company continue to maintain the quality of benefits IM3 @ School and followed by quality improvement IM3 @ School program by providing unique and innovative programs. Keywords: benefit, program, loyalty